Antisperm Antibody (ASA) Testing: Overview of Its Significance in Addressing Immunological Male Infertility - Ivan Angelo Albright; Bondan Winarno; Evi Tjahyono; Muhammad Adamas; Januar Alfred Poli; Pety Narulita; Sri Musta'ina (Indonesian Andrology and Biomedical Journal, 2026)
Background: Antibodies against sperm, known as ASA, have been found in infertile men as a potential cause of male infertility. Reviews: Several reasons for ASA production have been discovered, resulting from an abnormal interaction between mature germ cells and the immune system. The WHO manual 5th edition described ASA testing with mixed anti-globulin reaction and immunobead binding test, which is now included in the extended semen tests in the WHO manual 6th edition. The connection between ASA and infertility can be considered intricate. Sperm agglutination may suggest the existence of anti-sperm antibodies (ASA) but is not enough for diagnosing immunological infertility. Nevertheless, ASA can also be found even without sperm agglutination. Summary: ASA testing for immunological infertility is controversial, with limited evidence supporting its use and treatment options, and is not recommended as an initial step but might be considered in specific cases of natural conception attempts.